(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Corporate governance is "management management" or meta-management, as it encompasses the set of relationships between management, the board of directors, shareholders and shareholders of a company. Effective governance reduces the inappropriate consequences of conflicts of interest between managers and owners, such as the abuse of power, that is, the identification of corporate governance mechanisms that lead to financial performance and social legitimacy or the realization of set goals.